Strengthening the organizational climate in health facilities - Elgegren, Ursula (2015)
Measurement study and intervention of organizational climate in health facilities of the Department of Health, experimental research, pretest design, one group posttest, the sample consisted of 502 Peruvian Department of Health workers, aged between 22 and 69 years. The instrument used was the MS questionnaire of organizational climate. The study group participated in personal development workshops. The results are presented in the dimensions of Culture of Organization, Organizational Design and Human Potential.